(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Advanced research into synthetic chemistry has pointed out several organic compounds with antimicrobial potential. Schiff bases are one of such compounds. This research aims at the synthesis of a Schiff base out of a fairly common antibiotic amoxicillin and benzaldehyde. The synthesized compound was characterized by different spectroscopic techniques. It was also subjected to melting point determination, TLC and solubility tests. The Schiff base was screened for antibacterial and antifungal activities in-vitro by disc diffusion method. Bangladesh Pharmaceutical Journal 19(2): 211-214, 2016